New records of Orthotylinae (Hemiptera: Heteroptera: Miridae) from the Palaearctic Region - Konstantinov, Fedor V.; Namyatova, Anna A. (Zootaxa, 2009)
The following 22 species of Orthotylinae are recorded for the first time from various Palaearctic countries: Blepharidopterus diaphanus (Mongolia), Dryophilocoris luteus (Serbia), Excentricus planicornis (Mongolia), Globiceps flavomaculatus (Mongolia), Globiceps sordidus albipennis (Northern Kazakhstan), Malacocoris chlorizans (Georgia and Kyrgyzstan), Mecomma ambulans (Latvia and Mongolia), Orthotylus eleagni (Kyrgyzstan), Orthotylus flavosparsus (Mongolia and Turkmenistan), Orthotylus lenensis (Mongolia), Orthotylus nassatus (Armenia, Kyrgyzstan, and Uzbekistan), Orthotylus viridinervis (southern parts of European Russia and Ukraine), Platycranus eckerleini (Morocco), Anapus kirschbaumi (Mongolia and Uzbekistan), Chorosomella jakowleffi (southern parts of European Russia), Euryopicoris nitidus (Kyrgyzstan, Tajikistan, and Mongolia), Halticus apterus (Mongolia), Halticus obscurior (Uzbekistan), Halticus puncticollis (West Siberia), Labops sahlbergii (European and Asian parts of Kazakhstan), Platyporus dorsalis (Azerbaijan), and Strongylocoris leucocephalus (Mongolia).